MEASUREMENT OF POLICE EFFECTIVENESS IN THE DETECTION AND FIGHT OF CRIMES IN NIGERIA - Echeonwu, Macdonald Silas; Asiegbu, Victor Iheanyichukwu, Ph.D,; Omenka, Job Alobo (Journals Park Publishing, 2023)
The Nigeria Police Force is an entity created by the constitution with a mission to maintain a crime free society. The study investigated the Nigerian Police efficacy in crime detection and combat in Rivers State. Consequently, the research questions that guided the study were as follows: what is the degree of achievement by the Nigerian Police Force in crime detection and combat in Nigeria? What are the obstacles encountered by the Nigerian Police Force in crime detection and combat in Nigeria? The study used strain anomie theory as its theoretical framework and utilised both survey research design and simple random sampling approach, respectively. The research employed both primary and secondary data. The secondary data obtained from journals and textbooks were analysed using content analysis. The primary data collected from questionnaire items were presented in tables and analysed using the 4-point Likert scale, with a criterion mean standard of 2.50. The research results demonstrated that the Nigeria Police force has difficulties like inadequate funding, insufficient staff training, and a lack of modern crime-fighting equipment’s. In conclusion, the research, among others, suggests that there should be adequate budgetary provisions for the Nigeria Police Force, personnel should undergo modern combat and police training, as this would enhance their performance in delivering services.